Combining bulk stable H isotope (δ2H) measurements with fatty acid profiles to examine differential use of aquatic vs. terrestrial prey by three sympatric species of aerial insectivorous birds - Génier, Corrine S. V.; Guglielmo, Christopher G.; Hobson, Keith A. (Frontiers in Ecology and Evolution, 2022)
Aerial insectivorous songbirds such as swallows and martins have declined substantially in North America in recent decades. Aquatic-emergent insects provide more beneficial omega-3 fatty acids than terrestrial insects, and thus, diet quality is expected to vary among aerial insectivores with differential access to aquatic-emergent insects. We compared the stable hydrogen isotope (δ2H) values of feathers and bulk blood plasma fatty acids of nestling purple martins (Progne subis), tree swallows (Tachycineta bicolor), and barn swallows (Hirundo rustica), at lakeshore and inland sites near Lake Erie, Ontario, Canada. We found that diet quality differed between inland and lakeshore nesting habitats, but differences depended on species. Overall, purple martin and tree swallow nestlings had lower feather δ2H values, indicating a more aquatic-emergent diet, and lakeshore populations of both species had higher omega-3 fatty acid levels in their blood plasma compared to inland populations. Conversely, higher plasma levels of omega-6 fatty acids were found in inland birds. Tree swallows have a low omega-3 conversion efficiency from precursor substrates and so depend on aquatic subsidies to fulfill their nutritional needs. We suggest this may also be the case with purple martins. Barn swallows had the most positive feather δ2H values, regardless of proximity to the lakeshore, indicating a more terrestrial diet. However, barn swallow nestlings had consistently higher plasma omega-3 docosahexaenoic acid (DHA) regardless of nesting location, suggesting that barn swallows can efficiently convert omega-3 precursors into their beneficial elongated fatty acid chains. Our study indicates the benefit of combining plasma fatty acid compositional analyses with bulk feather δ2H values to decipher interspecific differences in adaptations to availability of aquatic-emergent insects.